REFERENSI ENDOFORA DALAM CERAMAH USTADZ ZAINUDDIN MUHAMMAD ZEIN - Sari, Dwi Sapta Elsa Nofita; Charlina, Charlina; Mustafa, M. Nur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study, entiled Endofora Reference in Lecture Ustadz Zainuddin Muhammad Zein. This study aims to describe the endofora reference in the lecture Ustadz Zainuddin Muhammad Zein. This type of research is all sentences that use endofora reference type either based on its reference position or by its object type contained in the lecture of ustadz zainuddin Muhammad zein. Data obtained by using techniques refer, recording techniques and record techniques, then, the dta were analyzed by identifying and classifying according to the reference endofora reference in the lecture of ustadz zainuddin Muhammad zein, endofora reference types found, among others, references of endofores based on reference anhapora and katafora and reference by object type references persona, demonstrative reference, and comparative reference. the kind of pronouns persona used among others saya, aku,-ku, kamu, -mu, engkau, kau, ia, dia, beliau, -nya, kita, mereka.the demonstrative pronominal types used are, for example, sini, sana, ini, itu, while the comparative pronouns used are the sama dan serupa.Keywords: Endofora references, lecture ustadz Zainuddun Muhammad Zein,anaphora, katafora.